Structural Analysis of the Novel Dima'un fi Qasr al-Chamra by Ehab Farouk Hosny: Important Cultural Stories in the History of Islamic Civilization in Spain - Somanudin, Somanudin; Wafiroh, Siti Atiatul; Wiwaha, Rizzaldy Satria; nuraini, Yeni; Sangidu, Sangidu (Institut Agama Islam Negeri Curup, 2023)
This research aims to conduct a structural analysis of the novel Dima'un Fi Qasr al-Chamra by Ehab Farouk Hosny. This novel raises an important cultural story in the history of Islamic civilization in Spain. It tells the story of a beautiful woman from Egypt, named Sarah, an archaeologist who researches Islamic heritage buildings both in her own country and in other countries. It tells the history of Andalusia, now Spain, starting from discovering a map buried in one of the rooms in Sultan Hasan's mosque in Cairo. The map was a secret document of the Alhambra belonging to the great scientist Al Zahrawi (Albucasis), containing a chemical composition to treat cancer. This paper has two main objectives: the practical and theoretical objectives. The realistic goal is to reveal the intrinsic and coherent elements and the interrelationship between one part and another. Meanwhile, the academic goal is to discover a secret document belonging to el-Zahrawi, a scientist, containing a cancer drug's composition. To remind readers that the discovery of personal papers, in any case, should not be announced in public because it can be dangerous and will cause various problems in obtaining certain benefits and goals. The theory used is a structural theory, which focuses on literary works viewed as a unified and integrated structure. The technical method is the structural method, which works structurally by revealing and describing the intrinsic elements in